2013
DOI: 10.1189/jlb.0613337
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 is an early and critical mediator in an animal model of uveitis induced by IRBP-specific T cells

Abstract: It is largely unknown how invading autoreactive T cells initiate the pathogenic process inside the diseased organ in organ-specific autoimmune disease. In this study, we used a chronic uveitis disease model in mice--EAU--induced by adoptive transfer of uveitogenic IRBP-specific T cells and showed that HMGB1, an important endogenous molecule that serves as a danger signal, was released rapidly from retinal cells into the ECM and intraocular fluid in response to IRBP-specific T cell transfer. HMGB1 release requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 51 publications
4
28
0
Order By: Relevance
“…A specific combination of cytokine signals leads to the differentiation of naïve T cells into different effectors (Th1, Th2 and Th17) and regulatory T cell subsets. T cells can release HMGB1 in response to several stimuli or cell-cell contact in co-cultures (Jiang et al, 2013; Kawahara et al, 2007). In addition, HMGB1 released from DCs regulates polarization of CD4+ T cells (Messmer et al, 2004) and mediates cell-cell interactions (Kohka Takahashi et al, 2013).…”
Section: Hmgb1 Functionmentioning
confidence: 99%
“…A specific combination of cytokine signals leads to the differentiation of naïve T cells into different effectors (Th1, Th2 and Th17) and regulatory T cell subsets. T cells can release HMGB1 in response to several stimuli or cell-cell contact in co-cultures (Jiang et al, 2013; Kawahara et al, 2007). In addition, HMGB1 released from DCs regulates polarization of CD4+ T cells (Messmer et al, 2004) and mediates cell-cell interactions (Kohka Takahashi et al, 2013).…”
Section: Hmgb1 Functionmentioning
confidence: 99%
“…To assess the function of the T cells from WT and C3aR/C5aR KO mice with EAU, we compared the efficacy of the same number of WT and KO T cells in inducing retinal inflammation in naïve recipient mice. Using an established protocol [36,37], we activated the IRBP-specific T cells in vitro by culturing splenocytes from WT and KO mice with EAU using the same concentrations of IRBP peptide, together with IL-23, for 3 d. We then enriched the activated (blasted) T cells by Ficoll centrifugation and adoptively transferred a fixed number of the in vitro-activated (blasted) WT or KO T cells into naïve recipient mice. We evaluated EAU development by indirect ophthalmoscopy.…”
Section: Adoptive Transfer Of In Vitro-activated C3ar/c5ardeficient Tmentioning
confidence: 99%
“…*P < 0.05. shown that elevation of HMGB1 in intraocular fluids has been shown to precede histopathologic changes in the EAU induced by adoptive transfer of uveitogenic T cells. 35 There were no significant differences in vitreous HMGB1 level and anterior and posterior segment inflammation scores between patients with ocular sarcoidosis treated with systemic corticosteroids and those without steroid treatment at the time of vitrectomy. These results suggest that vitrectomy was performed in the remission phase of uveitis in most of the sarcoidosis patients, irrespective of systemic treatment with corticosteroids.…”
Section: Discussionmentioning
confidence: 72%
“…In EAU, retinal cells release HMGB1 into the intraocular fluid via an interaction with pathogenic T cells, and systemic or local administration of anti-HMGB1 antibodies suppresses EAU by inhibiting pathogenic T-cell proliferation and their IFN-c and IL-17 production. 35 It is conceivable that Th1 cells that produce IFN-c promote release of HMGB1 in the vitreous in ocular sarcoidosis and that they are synergistically involved in the development of ocular inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation